Stylistic Analysis of the Song Kartonyono Medot Janji by Denny Caknan - Lestari, Dewi (Universitas PGRI Semarang, 2024)
The lyrics of this song are the lyrics of a dangdut song sung by Denny Caknan in Javanese. The interesting thing to study further is the use of diction and the theme using stylistics, namely by looking at the style of language used. The purpose of this study was to analyze the stylistics contained in the lyrics of the song